GAPs for the Florida Citrus Grower: Understanding the Principles of Good Agricultural Practices - Michelle D. Danyluk; Renée M. Goodrich-Schneider; Keith R. Schneider; Mark A. Ritenour; Timothy M. Spann (EDIS)
Growers are the first step in the farm-to-table food chain. Good Agricultural Practices (GAPs) refer to practices growers follow to prevent, minimize, or eliminate contamination and hazards to human health. Essential components of the GAPs process include careful planning, implementation, and documentation of required steps and procedures that together analyze and minimize risks imposed by biological, chemical, and physical hazards. The general guidelines presented in this document were developed by UF/IFAS for Florida citrus growers, in partnership with the citrus industry. This 8-page fact sheet was written by Michelle D. Danyluk, Renée M. Goodrich-Schneider, Keith R. Schneider, Mark A. Ritenour, and Timothy M. Spann, and published by the UF Department of Food Science and Human Nutrition, February 2012.